Metabolic disorder induces fatty liver in Japanese seabass, Lateolabrax japonicas fed a full plant protein diet and regulated by cAMP-JNK/NF-kB-caspase signal pathway. Issue 90 (July 2019) - Zhang, Y.; Chen, P.; Liang, X.F.; Han, J.; Wu, X.F.; Yang, Y.H.; Xue, M.
Abstract: A 10-week growth trial was conducted to investigate the effects of replacing dietary fishmeal with plant proteins on nutrition metabolism, immunity, inflammation and apoptosis responses in liver tissues of Japanese seabass, Lateolabrax japonicas (initial body weight = 10.42 ± 0.01 g). Two isonitrogenous and isoenergetic diets were formulated. A basal diet containing 54% fishmeal (FM), whereas another diet was prepared by totally replacing FM with a plant protein blend (PP) composed with soybean protein concentrate and cottonseed protein concentrate. Although essential amino acids, fatty acids, and available phosphorus had been balanced according to the FM diet profile, the significantly lower growth performance, metabolic disorder, and fatty liver symptom were observed in the PP group. Compared with the FM group, fish in the PP group showed significantly lower plasma free EAA level and PPV. Glucose metabolism disorder was expressed as the uncontrollable fasting glycolysis and pyruvate aerobic oxidation at postprandial 24 h with significantly up-regulated GK, PK and PDH genes expression, which potentially over-produced acetyl-CoA as the substrate for protein and lipid synthesis. Significantly reduced plasma GLU, but increased GC level, along with very significantly reduced liver GLY storage could be observed in the PP group. Plasma TG and hepatic NEFA contents were significantly decreased, but the hepatic TC content was very significantly increased in the PP group, in addition, hepatocyte vacuolation appeared. The significantly up-regulated cholesterol synthesis gene (HMGCR) expression but down-regulated bile acid synthesis gene (CYP7A1) expression could be the main reason for the fatty liver induced by cholesterol accumulation. The reduced plasma IgM content accompanied by the up-regulated mRNA levels of pro-inflammatory cytokines (TNFα and IL1β) and activated apoptosis signals of liver tissues were found in the PP group. The hyperthyroidism (higher plasma T3 and T4) and the accelerated energy metabolism rate decreased the growth performance in the PP group. The activated p65NF-kB may promote the hepatocytes apoptosis via the extrinsic pathway (caspase8/caspase3). Simultaneously, a "self-saving" response could be observed that activated cAMP promoted the lipolysis/β-oxidation process and up-regulated gene expression of anti-inflammatory cytokine IL10 via promoting CREB expression, further inhibited the over-phosphorylation of JNK protein, which might impede the intrinsic apoptosis pathway (caspase9/caspase3). In conclusion, the nutrient and energy metabolic disorder induced fatty liver related to the cholesterol accumulation in Japanese seabass fed full PP diet, which was under the regulation by cAMP-JNK/NF-kB-caspase signaling pathway. The hemostasis phosphorylation of JNK protein protected the liver tissues from more serious damage. Graphical abstract: Image 1 Highlights: Japanese seabass could well ingest the plant protein (PP) diet, but the growth performance and immunity were reduced. The PP diet induced the overall metabolic disorder, which further caused the inflammatory reaction and fatty liver. TNFα and IL1β activated the p65 NF-kB into hepatocyte nuclei and promote the exogenous apoptotic pathway in the PP group. The hemostasis phosphorylation of JNK protein dually regulated by cAMP-JNK/NF-kB-caspase signaling pathway. The hemostasis phosphorylation of JNK protein protected the liver tissues from more serious damage.